BIODEGRADASI ZAT WARNA REMAZOL YELLOW FG DALAM SISTEM SUSPENSI AKTIF - Gosal, Rosalia; Budiarsa Suyasa, I Wayan; Dwi Adhi Suastuti, GAM (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2018)
Remazol Yellow FG is used in the textile industry in the process of dyeing and chromatic system. The waste of Remazol Yellow FG is dangerous for ecosystem and human health if it is thrown into the environment. This research was conducted the application of waste execution that is biodegradation of Remazol Yellow FG dye in activated suspension. The aim of this research are : 1) to obtain the optimum time of microorganisms growth of sediment which taken from mangrove ecosystem of Serangan area, 2) to determine the optimum composition in declining the rate of Remazol Yellow FG waste, 3) to determine the rapid of Remazol Yellow FG rate decline, 4) to know effectivity and microbial system that play role in biodegradation process. The textile waste used in this research was artificial waste from Remazol Yellow FG dye with concentration of 49,126 mg / L. In the first phase, it observed the growth of microorganisms which is determined by determining the highest value of VSS (Volatile Suspended Solid) as the optimum time of bacteria capable of degrading Remazol Yellow FG . Furthermore, using the optimum time, the optimal composition is determined by observing the decrease levels of Remazol Yellow FG . The rate of decrease observed from the decreased levels of Remazol Yellow FG in biodegradation process for 7 days. The effectivity obtained from percentage of Remazol Yellow FG levels contained at the time of processing. Besides, there was an identification of microorganisms that take a role in biodegradation process of Remazol Yellow FG. The results showed that 12 hours is required to obtain the optimum time of microorganism growth with highest value 28000mg/L of VSS after added into means containing the Remazol Yellow FG . The optimum composition in decreasing Remazol Yellow FG rate were composition I consisting of 900 mL glucose, 1950 mL Remazol Yellow FG waste, and 150 mL suspended grown that can reduce levels of waste from 49,126 mg/L to 34,573 mg/L. Decreased levels of Remazol Yellow FG with anaerobic-aerobic treatment for 7 days decreased from 49,126 mg / L to 3,6039 mg / L and has 92,66% effectivity. The  identified bacteria and take dominant role in the process of biodegradation  are Bacillus sp, Coliform, Pseudomonas sp and Staphylococcus sp . Observation number of colonies in the early processing as amounted 2,84x102 CFU / mL, in the middle of processing time at 1,24 X102 CFU / mL, and at the end of biodegradation processing of 2,08x102 CFU / mL.